Percutaneous Thrombus Removal in a COVID-19–Infected Patient with Pulmonary Embolism - Nascimbene, Angelo; Basra, Sukhdeep S; Dinh, Kha; Patel, Jayeshkumar A; Gregoric, Igor D; Kar, Biswajit (Methodist DeBakey cardiovascular journal, 2021)
We present a case describing the use of the AngioVac system (AngioDynamics, Inc.) and SENTINEL™ cerebral protection system (SCPS; Boston Scientific) in a patient with COVID-19 who initially presented with a large deep-vein thrombosis of the left lower extremity, complicated by a pulmonary embolism. Although he initially improved with systemic alteplase, he later developed a second large clot diagnosed in transit in the right atrium. Within 12 hours from initial thrombolysis, this large clot wedged across an incidental patent foramen ovale (PFO), the atrial septum, and the cavotricuspid annulus. We emergently performed a percutaneous clot extraction with preemptive placement of the SCPS in anticipation of cardioembolic phenomenon. A large (> 10 cm) clot was extracted without complication, and the patient was discharged home. The combined use of SCPS and AngioVac in this case suggests a potential role for percutaneous treatment of severe and consequential thromboembolic disease, especially in patients with a PFO, and may be considered as an alternative and less-invasive option in patients with COVID-19. While cerebral embolic protection devices are approved for and widely used in transcatheter aortic valve replacement procedures, there is a theoretical benefit for use in percutaneous thrombolectomies as well.We present a case describing the use of the AngioVac system (AngioDynamics, Inc.) and SENTINEL™ cerebral protection system (SCPS; Boston Scientific) in a patient with COVID-19 who initially presented with a large deep-vein thrombosis of the left lower extremity, complicated by a pulmonary embolism. Although he initially improved with systemic alteplase, he later developed a second large clot diagnosed in transit in the right atrium. Within 12 hours from initial thrombolysis, this large clot wedged across an incidental patent foramen ovale (PFO), the atrial septum, and the cavotricuspid annulus. We emergently performed a percutaneous clot extraction with preemptive placement of the SCPS in anticipation of cardioembolic phenomenon. A large (> 10 cm) clot was extracted without complication, and the patient was discharged home. The combined use of SCPS and AngioVac in this case suggests a potential role for percutaneous treatment of severe and consequential thromboembolic disease, especially in patients with a PFO, and may be considered as an alternative and less-invasive option in patients with COVID-19. While cerebral embolic protection devices are approved for and widely used in transcatheter aortic valve replacement procedures, there is a theoretical benefit for use in percutaneous thrombolectomies as well.